A Normal Contact Stiffness Statistical Model of Joint Interface considering Hardness Changes - Donghua Yin; Xueliang Zhang; Shuhua Wen; Guosheng Lan; Yonghui Chen (Advances in Materials Science and Engineering)
Based on Kogut and Etsion’s finite element contact model (KE model) and citing the hardness geometric limit proposed by Jackson et al., the deformation stage of an asperity is re-divided, and a normal contact stiffness model of joint interface is established by using a statistical theory. The simulation results show that the normal contact stiffness of joint interface is a nonlinear function of the mean surface separation and decreases with the increase of the mean surface separation under different plasticity indexes. By comparing the normal contact stiffness model of joint interface considering hardness changes with the normal contact stiffness model of joint interface without considering hardness changes, it is found that, with the increase of the plasticity index, the difference between calculated results becomes larger.